Genome‐wide identification, expression analysis of auxin‐responsive GH3 family genes in maize (Zea mays L.) under abiotic stresses. Issue 9 (11th March 2015) - Feng, Shangguo; Yue, Runqing; Tao, Sun; Yang, Yanjun; Zhang, Lei; Xu, Mingfeng; Wang, Huizhong; Shen, Chenjia
Abstract Auxin is involved in different aspects of plant growth and development by regulating the expression of auxin‐responsive family genes. As one of the three major auxin‐responsive families, GH3 (Gretchen Hagen3) genes participate in auxin homeostasis by catalyzing auxin conjugation and bounding free indole‐3‐acetic acid (IAA) to amino acids. However, how GH3 genes function in responses to abiotic stresses and various hormones in maize is largely unknown. Here, the latest updated maize (Zea mays L.) reference genome sequence was used to characterize and analyze the ZmGH3 family genes from maize. The results showed that 13 ZmGH3 genes were mapped on five maize chromosomes (total 10 chromosomes). Highly diversified gene structures and tissue‐specific expression patterns suggested the possibility of function diversification for these genes in response to environmental stresses and hormone stimuli. The expression patterns of ZmGH3 genes are responsive to several abiotic stresses (salt, drought and cadmium) and major stress‐related hormones (abscisic acid, salicylic acid and jasmonic acid). Various environmental factors suppress auxin free IAA contents in maize roots suggesting that these abiotic stresses and hormones might alter GH3‐mediated auxin levels. The responsiveness of ZmGH3 genes to a wide range of abiotic stresses and stress‐related hormones suggested that ZmGH3s are involved in maize tolerance to environmental stresses.